Public Speaking Anxiety and English Language Competency of Bachelor of Secondary Education English Majors - Ma Fe B Reyes; Dialyn Samson; Carol A Tamayo; Jomari P Valeña; Maria Teresa M Rodriguez (Research Synergy Foundation, 2023)
This research aimed to determine the public speaking anxiety and English language competency of the Bachelor of Secondary Education English majors at Laguna State Polytechnic University Los Baños Campus. The study employed a descriptive correlation research design using a validated survey questionnaire to find the relationship between the variables. In the study's findings, the respondents' public speaking anxiety level had a standard deviation of 0.71 and was descriptively interpreted as